2020
DOI: 10.1017/s0144686x20000896
|View full text |Cite
|
Sign up to set email alerts
|

Qualities of the environment that support a sense of home and belonging in nursing homes for older people

Abstract: The aim of this study was to contribute with knowledge about how a sense of home and belonging is enacted and can be supported in everyday life, with a particular focus on the relationships that connect everyday life and the environment in nursing home contexts. The concepts ‘a sense of home’ and ‘belonging’ were chosen with the ambition to grasp values grounded in experiences and everyday practices, with an openness for various aspects that can support an enjoyable life and comfort for nursing home residents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 44 publications
(106 reference statements)
1
34
0
Order By: Relevance
“…There is a tension between enabling ARC residents with dementia to have their voices heard in research and the risk of inadvertent coercion. The power differential between staff, who have the most power, and residents, who have the least power, in institutional settings has been described by Goffman (1968) and others subsequently (Bridges et al, 2020;Johansson et al, 2020). When inviting people with dementia, particularly those who are residing in institutional settings, to participate in research, researchers must be cognizant of that power differential.…”
Section: Active Participationmentioning
confidence: 99%
“…There is a tension between enabling ARC residents with dementia to have their voices heard in research and the risk of inadvertent coercion. The power differential between staff, who have the most power, and residents, who have the least power, in institutional settings has been described by Goffman (1968) and others subsequently (Bridges et al, 2020;Johansson et al, 2020). When inviting people with dementia, particularly those who are residing in institutional settings, to participate in research, researchers must be cognizant of that power differential.…”
Section: Active Participationmentioning
confidence: 99%
“…The findings from this present study highlight the importance of common areas that offer opportunities for a variety of actions, activities, events, and atmospheres, which are potentially meaningful moments of everyday life for family members, residents, and staff. Previous research has shown how spatial dynamics that support such variety facilitate a sense of home and belonging in nursing homes ( Calkins, 2018 ; Johansson et al, 2022 ). In addition, previous research ( Calkins 2018 ; Falk et al, 2013 ; Fleming et al, 2016 ; Johansson et al, 2022 ) has emphasised that environments that support opportunities for variety in everyday life may be particularly important in nursing home contexts, since nursing home residents spend most of their time within the nursing home.…”
Section: Discussionmentioning
confidence: 99%
“…This preference was partly because the common areas provided proximity to the staff, which was appreciated by the spouses, especially as the residents’ dementia progressed ( Førsund & Ytrehus, 2018 ). Furthermore, earlier research has underscored the saliency of the arrangement of common areas in nursing homes for enabling person-centred care ( Edvardsson et al, 2010 ; Fleming et al, 2016 ), as well as a sense of home and belonging ( Johansson et al, 2022 ). Still, there is a scarcity of research exploring the perspectives of family members of residents regarding the physical environment of nursing homes.…”
Section: Introductionmentioning
confidence: 99%
“…While the meaning of home can be subjective, difficult to quantify, and differ from individual to individual (Fox O'Mahony 2012;Fleming and Kydd 2018;Fleming et al 2017), there are some commonalities to providing homely residential aged care facilities. Much of the research into the meaning of home for older people living in aged care has focused on the physical aspects of spaces, for example, accessible design, affordability, safety, attractive communal spaces, access to the outdoors, private spaces, and aesthetically pleasing buildings (Sims and Cornell 2020;Fleming and Kydd 2018;Mmako et al 2020), and how these physical spaces are used by staff and residents (Johansson et al 2020;Førsund et al 2018). However, physical environs alone do not make a place home if they constrain what an older person can do or how they feel about themselves (de Jonge et al 2011).…”
Section: Introductionmentioning
confidence: 99%